Book Review pH Responsive Membranes: Biomedical Applications (Journal of Applied Membrane Science & Technology, 2025)
Biomedical science is a broad interdisciplinary field that integrates biology and medicine, aiming to improve diagnosis, treatment, and disease prevention. Membrane technology plays a significant role in this domain, particularly in drug delivery, hemodialysis, chemical sensing, and the purification of pharmaceutical products. These include the recovery of antibodies and enzymes, protein concentration, and the reclamation of ultrapure water for processing and cleaning. As highlighted by the authors, pH-responsive membranes are typically composed of two main polymer groups: carboxyl-containing polyacids and pyridine-based polybases. These polymers swell and ionize differently depending on the surrounding pH, resulting in tunable permeability and selectivity. This book offers a novel consolidation of responsive membrane principles with a focus on biomedical applications. References span both foundational and emerging research, providing a balanced representation of state-of-the-art developments. It bridges theoretical transport models and real-world use cases, offering a valuable reference for material selection, design, and functional optimisation of pH-responsive membranes.